Model Peningkatan Kinerja Sumber Daya Manusia dengan Berbagi Pengetahuan berbasis Kemampuan Penggunaan Fintech - Rudi Joko Laksono; Widodo Widodo (Jurnal Dinamika Ekonomi & Bisnis, 2022)
This study aims to analyse the effect of knowledge sharing and knowledge gathering on the capability to use Fintech, and whether the capability to use Fintech affects the performance of human resources in Baitul Maal Wat Tamwil. This research was quantitative descriptive using path analysis method and data collection method used questionnaire distributed to Baitul Maal Wat Tamwil managers consisted of 96 respondents. Then verification analysis to test the hypothesis used Partial Least Squares (PLS) tool. The results showed that knowledge sharing and knowledge gathering had a significant positive effect on the capability to use Fintech services. The effect of the capability to use Fintech on the performance of human resources is also significantly positive.